Compulsive buying: the role of earlier-in-life events and experiences. Issue 4 (8th June 2015) - Grougiou, Vassiliki; Moschis, George; Kapoutsis, Ilias
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to examine the effects of earlier-in-life family events and experiences on the development of compulsive buying behavior in later life. Design/methodology/approach – The study is based on data collected from a self-administered survey of 285 young Greek adults. Findings – Young individuals appear to be particularly susceptible to their peers' evaluations of consumption matters. However, those who experience family disruptions and have a low socio-economic status are least likely to communicate with their peers about consumer matters, possibly as a self-protection coping mechanism. Contrary to previous findings, family communication styles promote rather than deter the development of compulsive tendencies, suggesting the influence of other macro-environmental factors upon the development of young adults' compulsive consumption tendencies. Social implications – Understanding the underlying mechanisms and contexts that promote the development of compulsive buying is imperative for deterring the onset of maladaptive consumption habits that have adverse effects on the individual and on society as a whole. Originality/value – Using the multi-theoretical life course paradigm, this study highlights the links between earlier-in-life experiences and social contexts to the onset and development of compulsive behaviors. The findings could assist public policy makers and parents to use strategies that would educate and protect future generations from developing compulsive consumption habits.